2023
DOI: 10.3390/ijms24021474
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anti-Inflammatory Properties of ZnO Nanoparticles Synthesized by a Green Method Using Sargassum Extracts

Abstract: The present work shows the synthesis of ZnO nanoparticles through a green method, using sargassum extracts, which provide the reducing and stabilizing compounds. The conditions of the medium in which the reaction was carried out was evaluated, that is, magnetic stirring, ultrasound assisted, and resting condition. UV-Vis, FTIR spectroscopy, and X-ray diffraction results confirmed the synthesis of ZnO with nanometric crystal size. The scanning electron microscopy analysis showed that the morphology and size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…Unlike the results reported by López-Miranda et al [45], it should be noted that control over the size and morphology of the synthesized nanostructures was obtained in this case. Although it is true that the methodologies used were not comparable, the results obtained could be attributed to the control of the precipitation reaction, followed by the growth, aggregation, self-assembly, and, finally, a stabilization of the products, all this due to the influence of the organic compounds such as flavonoids and polyphenols from this Sargassum alga.…”
Section: Physicochemical Characterization Of Zno Nanostructures Synth...contrasting
confidence: 82%
See 2 more Smart Citations
“…Unlike the results reported by López-Miranda et al [45], it should be noted that control over the size and morphology of the synthesized nanostructures was obtained in this case. Although it is true that the methodologies used were not comparable, the results obtained could be attributed to the control of the precipitation reaction, followed by the growth, aggregation, self-assembly, and, finally, a stabilization of the products, all this due to the influence of the organic compounds such as flavonoids and polyphenols from this Sargassum alga.…”
Section: Physicochemical Characterization Of Zno Nanostructures Synth...contrasting
confidence: 82%
“…Some products, such as blocks and shoe soles, have been made from Sargassum algae [ 42 ]. It has been reported that these Sargassum algae species have significant antioxidant activity, which can act as a reducing and stabilizing agent in synthesizing nanomaterials [ 45 , 46 , 47 ]. On the other hand, it has compounds that can be involved in the stabilization process, giving a particular morphology to the materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…97 Economical and efficient nanoparticle production (Fig. 14), such as CdS 98 and ZnS, 99 is achievable through Fusarium oxysporum's extracellular process, owing to its enhanced bioaccumulation of metal ions. 69 Recent studies reveal that besides fungi, yeast is utilized for biogenic synthesis due to its innate ability to assimilate toxic metal ions from the environment.…”
Section: Synthetic Approaches For Metal Sulfide Nanoparticlesmentioning
confidence: 99%
“…Zinc oxide nanoparticles (ZnO NPs) exhibit noteworthy efficacy against gram-negative and gram-positive bacteria. This effectiveness is attributed to their capacity to generate ROS, including cytotoxic effects on bacterial cells [2][3][4]. The remarkable antibacterial activity observed in ZnO NPs can be attributed to the possession of a low-energy band gap, leading to increased production of ROS [5].…”
Section: Introductionmentioning
confidence: 99%